Eksistensi Ulama dan Lembaga Pendidikan Islam pada Masa Kesultanan Aceh - Nurainiah, Nurainiah; Wardhani, Nia; Jeumpa, Nurul (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2023)
Ulama are used as spiritual leaders and authorities who serve as references for the people of Aceh on various socio-cultural issues and problems faced by society on a daily basis. During the time of Sultan Iskandar Muda, ulama had a very important position and role, as stated by Adat Bak Po Teumeureuhom, Hukom Bak Syiah Kuala, Resam Bak Laksamana, Qanun Bak Putroe Phang. Meaning, Customs in the Kingdom, Laws in the Syiah Kuala Ulama; Reusam to the Admiral, Qanun to the Queen of the Kingdom. In other words, ulama play the role of giving fatwas, so that every period there are ulama who accompany the government. The aim of this research is to determine the existence of Islamic scholars and educational institutions during the Aceh Sultanate. The type of research used is literature. The data collection technique was carried out through library research, namely by collecting several articles originating from journals and books relating to the existence of Islamic scholars and educational institutions during the Aceh sultanate. The data analysis technique in this research uses content analysis, namely analyzing books, journals and other literature related to research. The results of the research show that the existence of ulama during the Aceh Sultanate as fatwa givers. At the macro level, the ulama during Sultan Iskandar Muda's time received quite high positions, namely as qadhi (qadhi malikul adil at royal level and qadhi uleebalang at naggroe level). In other words, ulama have bargaining power in decision making in the kingdom, both worldly and spiritual matters as well as the development of science and culture which has given birth to Islamic educational institutions during the Aceh sultanate, namely meunasah, frameng, dayah, dayah teungku chik and jami`ah.